Home Based Exercise and Myofascial Release Technique Effectively Decrease Hamstring Tightness, Pain, and Disabilityin Eldery with Knee Osteoarthritis - Putu Ayu Sita Saraswati; Sayu Aryantari Putri Thanaya; Made Hendra Satria Nugraha; I Gusti Agung Ayu Ari Candra Laksmi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Osteoarthritis is one of the most common age-related diseases and is a primary cause of disability and pain. Cases of osteoarthritis cause pain, hamstring tightness, and limited range of motion, which reduce productivity and quality of life. Physiotherapy management for this condition may include Home-Based Exercise (HBE) and the Myofascial Release Technique (MRT).The purpose of this study was to compare the effectiveness of HBE and MRT in reducing hamstring tightness, pain, and disability caused by knee osteoarthritis in the elderly. This study employed an experimental design with a single-blinded randomized pre-test and post-test control group design. A total of 30 participants were recruited using consecutive purposive sampling and randomly divided into two groups. Knee disability was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), pain was measured using the Visual Analog Scale (VAS), and hamstring tightness was evaluated using the active knee extension test.The Paired T-Test revealed a significant reduction in knee disability, pain, and hamstring tightness before and after intervention in both the Myofascial Release Technique group (p < 0.001) and the Home-Based Exercise group (p < 0.001). However, Home-Based Exercise demonstrated greater effectiveness compared to the Myofascial Release Technique.